(Individual) Responsibility in decolonising the university curriculum - Le Grange, L. (South African Journal of Higher Education, 2021)
Since the “#RhodesMustFall” and “#FeesMustFall” student protests of 2015 and 2016 there has been much written about decolonisation in South Africa, particularly in relation to the curriculum. However, not much has been written about individual responsibility in the process of decolonisation, which Fanon (1967) argued is a necessary condition for decolonisation. In this article I argue that the autobiographical method, currere is one form of decolonisation. I use currere to document my own journey of decolonisation. I conclude that taking individual responsibility in decolonising the university curriculum involves a lifelong affair of unlearning and relearning from which no one is exempt because even those leading the decolonial project take in coloniality on a daily basis. Such a lifelong affair will involve multiple cycles of currere’s four steps so that currere, as a form of decolonisation, becomes a spiral of multiple cycles.